(untitled) (Research, Society and Development, 2024)
Dental treatments with aesthetic involvement drive the market towards an increase in the quality and diversity of materials, aiming to provide the highest satisfaction for both the patient and the dentist. Faced with limitations in metal-ceramic treatments, fully ceramic systems have evolved, enabling excellent aesthetic and functional results when appropriately indicated. The purpose of this case report is to describe a clinical case of oral rehabilitation in an aesthetic area through the replacement of a metal-ceramic crown with pure lithium disilicate ceramic (E-Max) for tooth 22. For the clinical success of the treatment, it was necessary to perform teeth whitening and dental recontouring with composite resin of the adjacent teeth prior to the fabrication of the definitive crown. Considering the techniques and materials used, the treatment performed was able to provide a result of clinical excellence, especially in this region that demands higher aesthetic requirements, offering satisfaction and restoring the patient’s self-esteem.